Nutritional Assessment of Patients with Liver Cirrhosis by Nutrition Screening Tool and Anthropometry at a Tertiary Care Center - Sherpa, Tshering W; Pathak, Rahul; Khadga, Prem K; Sharma, Sashi; Hamal, Rabin; Jha, Anurag (Journal of Institute of Medicine Nepal, 2019)
Introduction: Malnutrition is one of the most common complications of liver cirrhosis. Yet, little attention is paid in evaluating nutrition in this group of patients. This study aims to assess malnutrition among cirrhotic patients using a nutrition screening tool and anthropometry.Methods: This was a prospective, observational study of admitted patients with liver cirrhosis. In the study duration of 3months, 50 patients met the inclusion criteria and were included. Nutritional assessment was performed using the Royal Free Hospital Nutritional Prioritizing Tool (RFH-NPT), BMI and standard anthropometry including TSF,MUAC and MAMC.Results: The mean age was 51.56 ± 11.50 with a Male to Female ratio of 3:2. Chronic alcohol consumption (72%) was the most common etiology while management of tense as cites (40%) was the most common reason for hospital admission. 58% had Child Pugh Class C cirrhosis while the remaining 42% were Class B. The average MELD Nascore was 19.64 ± 6. Significant differences in anthropometric measurements including BMI, MUAC, TSF and MAMC were found between Child B and C cirrhosis. Similarly, those patients who had low, moderate and high-risk of malnutrition by the RFH-NPT had significant differences in anthropometric measurements between them.Conclusion: A significant number of patients had moderate to severe risk of malnutrition that correlated well with anthropometric measurements. The degree of malnutrition is parallel with the severity of liver disease among these patients. Both the RFH-NPT and anthropometry are relatively easy to perform and effective. Hence, they can be used as a practical means for identifying malnutrition among cirrhotic patients in routine clinical practice.